Sovereign bond yield spreads: A time-varying coefficient approach - Kerstin Bernoth; Burcu Erdogan (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We study the determinants of sovereign bond yield spreads across 10 EMU countries between Q1/1999 and Q1/2010. We apply a semiparametric time-varying coefficient model to identify, to what extent an observed change in the yield spread is due to a shift in macroeconomic fundamentals or due to altering risk pricing. We find that at the beginning of EMU, the government debt level and the general investors' risk aversion had a significant impact on interest differentials. In the subsequent years, however, financial markets paid less attention to the fiscal position of a country and the safe haven status of Germany diminished in importance. By the end of 2006, two years before the fall of Lehman Brothers, financial markets began to grant Germany safe haven status again. One year later, when financial turmoil began, the market reaction to fiscal loosening increased considerably. The altering in risk pricing over time period confirms the need of time-varying coefficient models in this context.
Keywords: C14; E43; E62; G12; H62; H63; 330; Sovereign bond spreads; fiscal policy; euro area; financial crisis; semiparametric time-varying coefficient model; nonparametric estimation